Elastiniu gumos treniruokliu poveikis tekvondo sportininku šoninio spyrio kokybei bei lavinamiems fiziniams gebejimams - Pundzevicius, V.; Paulauskas, R. (Sporto Mokslas-Sport Science, 2024)
The aim of this study was to evaluate the effect of elastic band training on the quality of young Taekwondo athletes` roundhouse kicks and their physical abilities. The study involved 21 high-level Taekwondo athletes aged 13-17 years. They were randomly divided into an experimental group (11 athletes) and a control group (10 athletes). The experimental group trained with elastic bands for 8 weeks, three times a week, performing roundhouse kicks. The control group followed the usual training program without elastic bands. The change in kick speed in the experimental group after 4 weeks of training with elastic bands averaged +2.1% for the right leg and 5.93% for the left leg (p < 0.001); after 8 weeks, the average change in kick speed was +11.71% for the right leg and +14.14% for the left leg (p < 0.001); 2 weeks after the end of the experiment, the average change in kick speed was +21.09% for both legs (p < 0.001). Furthermore, the study revealed that elastic band training did not negatively affect other physical abilities, such as vertical jump height and power, anaerobic-alactate muscle power, and 10-meter sprint speed. Elastic band training increases muscle engagement in movement, especially in the final stages of the movement when maximum force is required, which explains the significant improvement in roundhouse kick speed and power. Additionally, elastic band training creates additional resistance, promoting muscle adaptations such as increased motor unit engagement and better muscle coordination (Chiu et al., 2003; Tillin & Bishop, 2009). Although the study results are positive, the study has certain limitations. The small group of athletes and the limited duration of the study restrict the generalization of the results. In the future, it would be beneficial to conduct long-term studies with larger groups of athletes. In summary, elastic band training is an effective method for improving the speed and power of Taekwondo athletes` roundhouse kicks without reducing other physical abilities.